036 Nerve excitability and motor unit number estimation: early biomarkers of nerve involvement in hereditary amyloidosis (ATTRv). (23rd August 2021) - Carroll, Antonia; Lin, Cindy; Park, Susanna; Simon, Neil; Reilly, Mary; Vucic, Steve; Kiernan, Matthew
Abstract : Objective: Gene silencing treatments for hereditary transthyretin amyloidosis (ATTRv) have recently been developed with dramatic improvements observed in patient outcomes. However, the optimal time to initiate treatment is not yet known. The aim of this study is to explore the pathophysiological progression of neuropathic features of ATTRv using nerve excitability and motor unit number estimation. Methods: We prospectively recruited 14 symptomatic patients and 7 asymptomatic carriers and with varied TTR mutations and compared these to 21 healthy controls. Nerve excitability properties of ulnar motor and sensory axons, and ulnar-ADM motor unit number estimation was collected. Results: 'Fanning in' of threshold electrotonus was observed in the motor axons of symptomatic ATTRv patients, suggestive of membrane depolarisation. Motor unit number estimation demonstrated a significant reduction in mean unit number between symptomatic and asymptomatic ATTRv patients (p =0.04), with declines seen according to FAP stage and PND score. Significantly increased hyperpolarising current/threshold gradients were seen in sensory axons between symptomatic ATTRv patients and healthy controls (p=0.002), suggesting that upregulation of inwardly rectifying conductance may underlie sensory symptoms and neuropathic pain in ATTRv amyloidosis. Conclusions: These findings suggest that ulnar nerve excitability and motor unit number estimation could be used as a tool to identify early nerve disease in ATTRv and monitor progression.